Desenvolvimento de membranas com lacases por imobilização do extrato enzimático de Pleurotus sajor-caju - Rasera, Kátia (My University, 2014)
Laccases (EC 1.10.3.2) are phenol-oxidase enzymes associated to the degradation of lignin and a wide variety of recalcitrant compounds, such as xenobiotics and different types of dyes. Laccases catalyze the oxidation of various aromatic compounds with the concomitant reduction of oxygen to water. In this work, the results of immobilization of Pleurotus sajor-caju PS 2001 laccases in polyamide 6,6 (PA) and polysulfone (PSU) films, using glutaraldehyde as linking agent, are presented. The enzymatic solution containing laccases was obtained from solid medium with Pinus spp sawdust cultivated with P. sajor-caju. The proteins present in this solution were immobilized in PA and PSU films The immobilization process was studied with respect to the optimum pH, and the films were evaluated to determine the protein content and laccase activity. PA membranes showed higher laccase activity than PSU ones. With immobilized enzymes, a reduction of the optimum pH for laccase activity was observed, using acetate buffer and a increase using Mcllvaine buffer. The higher laccase activity was achieved after 6 h of immobilization, at a reaction temperature of 30°C, under agitation, for both PA and PSU films. Discolouration of approximately 90% of solution 25 mg.L-1 of the dye Reactive Blue 220 was verified, after 24 hours of reaction, using membranes of PA with the immobilized enzyme. Approximately 50% of the discolouration would be attributed from the adsortion process of the dye for the PA membrane. Similar results had been gotten with the use of the dye Remazol Brilliant Blue R (RBBR), with addition of Reactive Blue 220. Discolouration without addition of the Reactive Blue was not observed, suggesting a similar action to a mediator, providing the discolouration of the RBBR. Although to be observed immobilized activities of lacases in the membranes of PSU, using ABTS as substratum, discolouration of the analyzed corantes was not observed.
As lacases (EC 1.10.3.2) são fenol-oxidases associadas à habilidade de degradar a lignina e outros compostos recalcitrantes, como xenobióticos e vários tipos de corantes sintéticos. Lacases catalisam a oxidação de vários compostos aromáticos com concomitante redução do oxigênio a água. Neste trabalho são apresentados os resultados de imobilização do extrato de lacases de Pleurotus sajor-caju PS2001 em filmes poliméricos de poliamida 6,6 (PA) e polissulfona (PSU), utilizando glutaraldeído como agente de ligação. A solução enzimática de lacases foi obtida em meio sólido contendo serragem de Pinus spp cultivado com P. sajor-caju. As proteínas da solução enzimática foram imobilizadas em filmes de PA e PSU. O processo de imobilização foi estudado quanto ao pH ótimo, sendo os filmes caracterizados quanto à quantidade de proteínas imobilizadas e atividade de lacases. As membranas de PA apresentaram maior atividade de lacases quando comparadas com as de PSU. Observou-se uma redução do pH ótimo para atividade de lacases imobilizadas, utilizando-se o tampão acetato e um aumento em tampão Mcllvaine. A maior atividade de lacases foi obtida após 6 h de imobilização, em reação a 30°C, com agitação constante, tanto para os filmes de PA quanto para os de PSU. Verificou-se descoloração de aproximadamente 90% da solução 25 mg/L do corante Reactive Blue 220, após 24 horas de reação, utilizando membranas de PA com a enzima imobilizada. Aproximadamente 50% da descoloração obtida deve-se a adsorção do corante pela membrana. Resultados semelhantes foram obtidos com a utilização do corante Remazol Brilliant Blue R (RBBR), com adição de Reactive Blue 220. Não foi observada descoloração sem adição do Reactive Blue, sugerindo uma ação semelhante a um mediador, proporcionando a descoloração do RBBR. Apesar de serem observadas atividades de lacases imobilizadas nas membranas de PSU, utilizando-se ABTS como substrato, não foi observada descoloração dos corantes analisados.
Keywords: Microbiologia; Lacase; Fungos; Solução enzimática; Biotecnologia; Pleurotus sajor-caju; Corantes; Descoloração; Laccase; Fungus; Enzymatic solution; Biotechnology; Pleurotus sajor-caju; Colorifics; Discolouration